THE FABRICATION OF TEST STRIP FOR SIBUTRAMINE HCl DETECTION IN SLIMMING TRADITIONAL HERBAL MEDICINE - Robi'atul Andawiyah; Novrynda Eko Satriawan; Jumaati (Jurnal Kimia Riset, 2023)
The development of an optical sensor-based test strip for the detection sibutramine HCl adulteration in traditional herbal products has been studied. The medium of the test strip was cellulosic paper immobilized with Dragendorff’s reagent and tetraethyl orthosilicate (TEOS) as the precursor using the sol-gel method. The presence of sibutramine HCl changed the color of the test strip from yellow to orange-red. The change in color was scanned and converted to RGB values using the ImageJ software. The intensity of the RGB value correlates with the concentration of the analyte. The performance of the test strip had good linearity in the range of 0,1-1,5 mM of sibutramine HCl, and the correlation coefficient (R) was 0,9872. The limit of detection, limit of quantification, precision (% RSD), and percentage of accuracy were 0,2 mM, 0,8 mM, less than 5%, and approximately 80-90%, respectively. The strip test is low cost and simple. Thus, it can be used as an alternative to detect sibutramine HCl in traditional herbal products.